Characteristics of quantitative dynamic contrast-enhanced magnetic resonance imaging for orbital space-occupying lesions: A retrospective case series study - Liang Zhao; Zhenfeng Guo; Xiaodong Ji; Fengyuan Sun; Shuang Xia (PLoS ONE, 2025)
Objective This study aimed to compare the differences in the quantitative parameters of quantitative dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) across various types of orbital space-occupying lesions and to explore the diagnostic efficacy of DCE-MRI in the diagnosis of malignant orbital tumors.Meanwhile,to compare the differences in the quantitative parameters of DCE-MRI across vascular malformations, benign tumors, and malignant orbital lesions,and to explore the diagnostic efficacy of DCE-MRI introducing a novel grouping strategy that distinguishes vascular malformations from solid tumors. Methods In this retrospective case series study, patients were classified into three groups: vascular malformations, benign lesions, and malignant lesions. We analyzed the differences in the quantitative parameters and time-intensity curve (TIC) profiles among the three groups. The diagnostic efficacy of the quantitative parameters in the diagnosis of orbital malignant lesions was analyzed using receiver operating characteristic (ROC) curves. Results The differences in TIC compositions among the three groups were statistically significant (P < 0.05).The differences in volume transfer constant(Ktrans) value,rate constant(Kep) value,and area under curve(iAUC) among the three groups exhibited statistically significant differences (P < 0.05). All three diagnostic parameters(Ktrans, Kep, and iAUC) demonstrated effectiveness in diagnosing malignant lesions. The area under the ROC curve values for Ktrans, Kep, and iAUC were 0.759, 0.764, and 0.752, respectively, indicating adequate diagnostic value. Conclusions The composition ratios of the TIC for vascular malformations, benign lesions, and malignant lesions differed considerably. Ktrans, Kep, and iAUC can serve as valuable references for the differential diagnosis of orbital space-occupying lesions.